Regional and aggregate economic consequences of environmental policy - Tom Schmitz; Italo Colantone; Gianmarco I. P. Ottaviano (Fondazione Eni Enrico Mattei (FEEM), 2024)
This paper shows how to combine microeconometric evidence on the effects of environmental policy with a macroeconomic model, accounting for general equilibrium spillovers that have mostly been ignored in the literature. To this end, we study the effects of a recent US air pollution policy. We use regression evidence on the policy's impact across industries and local labor markets to calibrate a quantitative spatial model allowing for general equilibrium spillovers. Our model implies that the policy lowered emissions by 11.1%, but destroyed approximately 250'000 jobs. Ignoring spillovers overestimates job losses in polluting industries, but underestimates job losses in clean industries.
Keywords: E24; Q50; Q53; 330; Environmental Policy; Employment; Trade; Clean Air Act